Profile of netarsudil ophthalmic solution and its potential in the treatment of open-angle glaucoma: evidence to date - Dasso L (Dove Medical Press, 2018)
Lily Dasso, Tala Al-Khaled, Sriram Sonty, Ahmad A Aref Department of Ophthalmology and Visual Sciences, Illinois Eye & Ear Infirmary, University of Illinois at Chicago College of Medicine, Chicago, IL, USA Abstract: Netarsudil ophthalmic solution is a novel topical intraocular pressure (IOP)-lowering agent that has recently been approved by the US Food and Drug Administration (FDA) for the treatment of ocular hypertension and open-angle glaucoma. Its unique pharmacology allows for IOP lowering as a result of direct reduction in trabecular outflow resistance in addition to a decrease in episcleral venous pressure and aqueous humor production. The efficacy of netarsudil has been shown in animal studies and human clinical trials. It has been shown to be noninferior to the therapy with topical timolol in individuals with baseline IOP <25 mmHg. Importantly, netarsudil has been shown to reduce IOP to the same degree, regardless of baseline levels. There are no known systemic safety issues associated with netarsudil. The most common local adverse effects relate to conjunctival hyperemia. The once-daily dosing schedule is advantageous for individuals who have difficulties with medication adherence. Further studies of a combination of netarsudil and latanoprost agents are currently underway. Keywords: glaucoma treatment, Rho kinase, intraocular pressure lowering, glaucoma medical therapy